Outbreak of Salmonella Typhimurium ST19 linked to passerine birds and cats in Norway, March to July 2024 - Hilde Marie Lund; Lin T. Brandal; Liz Ertzeid Ødeskaug; Heidi Lange; Polina Katsiouleri; Gro S. Johannessen; Bjarne Bergsjø; Åsne Sangolt; Rikard Dryselius; Nadja Karamehmedovic; Henry Kuronen; Anni Vainio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose In June 2024, a genomic cluster of seven Salmonella Typhimurium - sequence type 19, and cluster type 21092 - was detected in Norway, triggering a national outbreak investigation. Methods Information about new cases was collected from the Norwegian Surveillance System for Communicable Diseases and the database at the National Reference Laboratory for Enteropathogenic Bacteria (NRL) at the Norwegian Institute of Public Health (NIPH). Microbiological analyses were conducted by NRL at NIPH for human samples and at the Norwegian Veterinary Institute for animal samples. Epidemiological data was collected through interviews. International notification was sent via EpiPulse. Results Eleven cases in total, sampled between March 6 and July 11, 2024, were identified across Norway. The median age of affected individuals was three years. Notably, 73% of the cases reported prior contact with cats or passerine birds. The outbreak strain was also detected in a faecal sample from a cat belonging to one of the affected households, suggesting an animal source. Concurrently, Finland and Sweden reported five and six cases, respectively, involving the same outbreak strain. Several of these individuals also reported contact with cats or birds. Conclusions Passerine birds are a well-documented reservoir for S. Typhimurium in the Nordic region, often leading to transmission to both cats and humans. This outbreak highlights the role of animal exposure in the spread of S. Typhimurium and emphasize the need for timely, targeted public health communication on infection prevention measures.